A REVIEW OF BURGELMAN AND GROVE’S CONCEPT OF STRATEGIC DISSONANCE - Ng, Huey Miin; Chee, How Liau (INTI International University, 2023)
Strategic dissonance, a concept central to the field of strategic management, encapsulates the inherent challenges organizations face in maintaining alignment between their intended strategies and the actual execution of those strategies. This phenomenon arises from dynamic interactions between external environmental changes and internal organizational dynamics, often resulting in a divergence between strategic aspirations and realized outcomes. This abstract explores the key dimensions of strategic dissonance, including the tension between intentions and actions, the impact of environmental shifts, the influence of organizational inertia, and the necessity for continual learning and adaptation. Addressing strategic dissonance requires organizations to navigate a complex landscape, embracing flexibility, responsiveness, and a proactive approach to strategy execution. The ability to recognize and reconcile strategic dissonance is integral to organizational agility and sustained competitiveness in a rapidly evolving business environment. This article review serves as a foundation for further exploration and analysis of the multifaceted nature of strategic dissonance and its implications for strategic management.